VARIOUS DIMENSIONS OF LABOUR AND FARMER LIFE IN CONTEMPORARY HINDI POETRY - Ranga, Reena; Shukla, Ajay Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The foundation of social, cultural and political life of any country is its economic condition. Strong, well-planned and systematic economic development accelerates the social order and progress of the country. Today, just as the status of a person is judged by looking at his economic condition, similarly, on the international platform, the development status of a nation is estimated on the basis of its economic development. In our country, the farmers and the working class have a special role in taking the flow of development forward, but their condition is very pathetic today. In the present times, the policies of globalization and the looting tendency of the capitalist people have exploited the lower class a lot. After independence, many laws were made to stop the exploitation of farmers and workers and to give them economic strength, but due to capitalist influence and government weakness, their exploitation continues even today. According to Dr. Shivkumar Sharma, there are only two castes in this world - the exploiter and the exploited. The exploiting class traders, landlords, industrialists are trying to maintain the capitalist system in the name of destiny and as long as this capitalist system remains, the end of exploitation is impossible.